If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y = 8 + 0 + 8y Combine like terms: 8 + 0 = 8 6y = 8 + 8y Solving 6y = 8 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 6y + -8y = 8 + 8y + -8y Combine like terms: 6y + -8y = -2y -2y = 8 + 8y + -8y Combine like terms: 8y + -8y = 0 -2y = 8 + 0 -2y = 8 Divide each side by '-2'. y = -4 Simplifying y = -4
| y=-7.36x-14354.33 | | 9k=18-3k | | 11x+19=107 | | 2.4x+6=16 | | 16x+2=8x | | 3y=4x+28 | | 0.5y-0.5=9 | | x(7)=91 | | 10+3+8+5-7-8= | | X^2+34x+289=0 | | 6x^2-6x+9=0 | | 3,7/8-2,3/16+3/8= | | 4x-2(4x-17)=10 | | -162=-7x-5(-6x-9) | | 17-8+3= | | -7(-7x+4)=-322 | | 5+3-7= | | -5-3-2= | | 6x+2(4x+13)=-58 | | -5(-6x+10)=-320 | | y-3x+11=0 | | -82=4x-6(-x+2) | | 3x+5x+7x= | | -56-9x=63-2x | | 8-7x=72-21x | | 6x-3y=13 | | 61-4x=8x-95 | | 3(5x-2y+4z)= | | 119-3x=5x+15 | | -28=-6x+26 | | lg(lg(x))=0 | | v+x=w+w |